Basic biomechanics of the musculoskeletal system - Nordin, Margareta; Frankel, Victor H. (Victor Hirsch), 1925-; Frankel, Victor H. (Victor Hirsch), 1925- (Philadelphia : Lea & Febiger, 2022)
Lippincott (R) Connect Featured Title Purchase of the new print edition of this Lippincott (R) Connect title includes lifetime access to the digital version of the book, plus related materials such as videos and multiple-choice Q and A and self-assessments. Clinically focused, clearly written and vibrantly illustrated, this introductory text equips students with a working knowledge of the force-motion relationship within the musculoskeletal system and the use of biomechanical principles in the evaluation and treatment of musculoskeletal dysfunction in clinical settings. Content progresses logically, introducing the basic terminology and concepts of biomechanics and providing focused perspectives on the biomechanics of tissues and structures, the biomechanics of joints and applied biomechanics - with case studies throughout to integrate biomechanical knowledge into clinical training for patient care. This updated 5th Edition of Basic Biomechanics of the Musculoskeletal System highlights the global relevance of musculoskeletal biomechanics and features new full-color images that demonstrate biomechanical movement with vivid detail. NEW! Two new chapters familiarize students with biomechanical approaches to the thoracic spine and rib cage, and typical postures (such as squatting) and their biomechanical impact upon indigenous people throughout the world. UPDATED! Revised content throughout acquaints students with the most up-to-date and clinically relevant perspectives. NEW! Full-color illustrations clarify structures and movements with engaging detail. Clinical case studies help students link biomechanical knowledge to practical applications. Lippincott (R) Connect features: Lifetime access to the digital version of the book with the ability to highlight and take notes on key passages for a more personal, efficient study experience. Carefully curated resources, such as interactive diagrams, video tutorials, organ sounds, and self-assessment, all designed to facilitate further comprehension. Lippincott (R) Connect also allows users to create Study Collections to further personalize the study experience. With Study Collections you can: Pool content from books across your entire library into self-created Study Collections based on discipline, procedure, organ, concept or other topics. Display related text passages, video clips and self-assessment questions from each book (if available) for efficient absorption of material. Annotate and highlight key content for easy access later. Navigate seamlessly between book chapters, sections, self-assessments, notes and highlights in a single view/page
Revised edition of: Basic biomechanics of the skeletal system/Victor H. Frankel, Margareta Nordin. 1980
Includes bibliographical references.
Keywords: Human mechanics; Biomechanical Phenomena